Relaţia tată-fiu în textul dramatic Ivanca de Lucian Blaga / The Father-Son Relation in Lucian Blaga"s Theatrical Play "Ivanca" - Georgeta Orian (Incursiuni în imaginar)
Lucian Blaga's theatrical plays have always been open to mythological interpretations. The text of the play 'Ivanca' is prone to interpretation frames such as Oedip's complex: the rivalry with the same-sex parent, in particular with the male one, the sexual tension which is felt amongst the three main characters of the play (the Father, Luca - the Son, and Ivanca), the solving of the the conflicting situation by Doctor Dinu's actions to reveal the complex, but also the Freud-Jung synthesis. The present paper follows the coordinates of the relation between the two characters, the Father and the Son, resorting to a mythological, symbolical and psycho-analytical frame analysis.